On (?,f)-statistical boundedness of order ? - Temizsu, Fatih; Et, Mikail; cinar, Muhammed; Kandemir, Hacer Sengul (Taylor & Francis Inc, 2022)
The main purpose of this work is to introduce and examine the concept of (lambda,f)-statistical boundedness of order alpha and give the relations between some known concepts and (lambda,f)-statistical boundedness of order alpha.
Keywords: Statistical boundedness; statistical convergence; modulus function